Fishvax anti-bacterial fish oral vaccine - Amparo, Ruel T.; Aquinde, Jaime Jr. E.; Ramones, Don Jazzper J.; Tanpho, Richard E.
The feasibility study of Fishvax, a company that produces fish oral vaccines for fish feed companies, aims to determine the feasibility of the commercialization of the fish oral vaccine. The product plans to introduce a more effective and efficient way to vaccinate tilapia fish by using file montmorillonite day to encapsulate the vaccine. The use of an encapsulated vaccine ensures that the vaccine reaches the immunization cells of the fish and that the vaccine is not dissolved in the digestive tract. The product is to be sold to fish feed companies, who will mix the oral vaccine with the fish feeds they produce. The pelleted vaccine will then be sold to fish farms. The targeted fish feed companies are located in the Central Luzon and CALABARZON Region, where more than 70% of tilapia is produced through fish farms. The product that will be sold to the fish feed companies is priced at approximately PhP 104 per liter of vaccine solution. For one ton of tilapia (3,OCX) heads of tilapia), 23 liters of vaccine is required, making the vaccine around PhP 2,390 per ton of tilapia The targeted market share, amount of vaccine required to be produced and forecasted revenues are given in the table: The initial investment for the company is about PhP 18,000,000. This will cover the capital investment (machinery, equipment) as well as the operating expenses for the first year (wage, rent, utilities, raw materials, etc.). In order to fund this project, a combination of private placement (70%), debt financing (25%) and proponent funding (5%) will be utilized. Based on the project financial statements for the first five years of operation, the net present value (NPV) is given in the table below (together with the necessary assumptions): The socio-economic analysis considers the non-financial benefits and costs incurred by the company to external entities, such as the government. Factors taken into consideration include taxes paid to the government and the carbon footprint made by the company. Based on the marketing, technical, financial and social-profitability analyses of the Fishvax company, it was determined that the commercialization of the fish oral vaccine should be pursued in order to attain the benefits and goals of the product.